Mecanismos da atividade tripanocida do elatol em tripomastigotas de Trypanosoma cruzi - Desoti, Vânia Cristina (2012)
Chagas' disease is an illness caused by Trypanosoma cruzi parasite, which affects millions of people on Latin America. The available drugs for treatment of this infection cause serious side effects and has variable efficacy especially in the chronic phase of the disease. In this context, natural products have shown good potential for the discovery of new chemotherapy for the treatment of this infection. Recently our group reported the activity of elatol, extracted from red macroalgae Laurencia dendroidea, present in brazilian coast, on T. cruzi. This trypanocidal activity might be a result of morphological and ultrastructural alterations revealed by electronic microscopy. Thus, the proposal of this work was to study the possible mechanisms of action and cell death pathways involved in the trypanocidal activity of elatol. Our results showed that treatment of trypomastigotes of T. cruzi with elatol induced changes in mitochondrial membrane potential, changes in cell membrane integrity, increase in the formation of mitochondrial superoxide anion, lipid peroxidation, DNA fragmentation, decreased cell volume and formation of autophagic vacuoles. These results suggest that the trypanocidal action of elatol involves multiple events that culminate in the death of T. cruzi. Our hypothesis is that the mitochondrial changes would be a crucial event that determines distinct biochemical pathways by inducing different types of cell death.